Eksplorasi Kesiapan Guru Sekolah Dasar Generasi Milenial-Z Menghadapi Pendidikan Society 5.0 - Grace Neolaka; Risa Fitria (Jurnal Elementaria Edukasia, 2024)
The era of society 5.0 has been entered by many developed countries. Indonesia, as a developing country, also has the same opportunity to enter the era of society 5.0. Therefore, an approach through the education system needs to be done, especially in preparing teachers in Indonesia. Millennial teachers born in 1981-2000 are future teachers and hope for Indonesia. They are the demographic bonus and the largest productive age group in Indonesia. This generation of teachers will face the education system in the era of society 5.0. This study explores the results of the self-reflection of millennial elementary school teachers on their readiness to face the education system in the period of society 5.0, specifically on technology mastery and students' understanding ability. Data were collected through unstructured interviews with 6 primary school teachers at millennial age in different schools to help them reflect on themselves and then analyzed using descriptive analysis. The results show that the readiness of elementary school teachers at the millennial age in terms of mastering technology is based on three self-conditions, namely self-confidence, the adaptability, and is relied on by colleagues. These three conditions of self in terms of mastery of technology are interconnected with each other. Meanwhile, in terms of student's ability to understand students, their self-readiness is based on two conditions, namely understanding one's own constraints in order to understand students and finding ways to relate to students. This research is limited to only two conditions, namely mastery of technology and the ability to understand students, which are included in teachers' pedagogic and professional competencies. This study also recommends several future teacher professional development research practices.